Dead aid : why aid is not working and how there is a better way for Africa - Moyo, Dambisa (Farrar, Straus and Giroux, 2009)
In "Dead Aid," Dambisa Moyo describes the state of postwar development policy in Africa that has channeled billions of dollars in aid but failed to reduce poverty and increase growth. She offers a new, more hopeful vision of how to address the desperate poverty that plagues millions.